Sedimentation history of the Paleoproterozoic Singhbhum Group of rocks, eastern India and its implications - De, S.; Mallik, L.; Mazumder, Rajat; Chatterjee, P.; Ohta, T.; Saito, S.; Chiarenzelli, J. (Elsevier BV, 2016)
This paper reviews the sedimentological, geochemical and stratigraphic characteristics of the Paleoproterozoic Chaibasa and Dhalbhum Formations (the Singhbhum Group) of eastern India and presents a comparative study with other Paleoproterozoic lithostratigraphic units of India. Both the formations are enitrely siliciclastic and deformed and metamorphosed, genererally at greenschist to upper amphibolite facies. The older Chaibasa Formation consists of sandstone, shale and sandstone-shale interbanded (heterolithic) facies. It conformably overlies the Late Archean-Paleoproterozoic Dhanjori Formation of terrestrial (alluvial fan-fluvial) origin. The Lower Chaibasa Member formed in a marine setting; the shale and heterolithic facies formed in a continental shelf setting below and above the storm wave base, respectively. The sandstone facies formed in a subtidal setting during sea level fall. In contrast, the Upper Chaibasa Member formed in a shallow-marine setting; both the shale and heterolithic facies formed above the storm wave base.In significant contrast, the overlying Dhalbhum Formation is dominated by finer clastics with much lower proportion of sandstones. The base of the terrestrial Dhalbhum Formation is a sequence boundary (unconformity). Sedimentary facies analysis clearly shows two broad facies association of terrestrial origin (fluvial and aeolian). The aeolian facies association overlies the fluvial facies association. The Dhalbhum sandstones show typical REE pattern of quartz dilution with lower concentrations compared to the mudstones. The Dhalbhum finer clastics mimic typical REE patterns resembling abundances in the continental crust. Rare earth element plots display a good match with Post-Archean Australian Shales (PAAS) including similar concentrations, steep negative slope for LREEs, negative Eu anomaly, and nearly flat HREES. The Singhbhum Paleoproterozoic succession is devoid of both chemical sediments and Paleoproterozoic glacial deposits in contrast to neighboring cratons.